Recent developments towards the synthesis of paroxetine: A 3, 4-disubstituted piperidine. Issue 25 (19th June 2020) - Jana, Samaresh; Sarkar, Sohini; Morris, Scott A.
Abstract: Paroxetine is a trans -3, 4-disubstituted piperidine compound that exhibits important medicinal properties. Over the past few decades, various strategies have been revealed in application to its synthesis. This review will highlight some of the synthetic approaches developed for paroxetine in past ten years. The goal of this review is to showcase recent strategies used to synthesize paroxetine with the anticipation that other novel syntheses will be revealed in the near future. Graphical abstract: Image 1